Extramedullary relapse of acute lymphoblastic leukemia treated with a CAR-T cell therapy bridge to unrelated cord blood transplantation: a case report and review of the literature - Li, Huibo; Liu, Jie; Guo, Dan; Zhao, Yanqiu; Li, Qi; Qi, Sen; Hou, Jinxiao; Zhang, Jianping; Fan, Shengjin (Frontiers in Oncology, 2025)
Extramedullary relapse of acute lymphoblastic leukemia (ALL) is usually associated with poor prognosis. Chimeric antigen receptor T cell (CAR-T cell) therapy followed by allogeneic hematopoietic stem cell transplantation is beneficial for relapsed/refractory (r/r) B cell acute lymphoblastic leukemia (B-ALL). Here, we report a B-ALL patient with extramedullary relapse involving several organs, including multiple lymph nodes and the breast, kidney, uterus and pancreas. After treatment with CAR-T cell therapy, positron emission tomography/computed tomography (PET/CT) revealed that she went into remission, with an almost undetectable tumor mass. She subsequently received unrelated cord blood transplantation (UCBT). Although she achieved minimal residual disease (MRD)-negative remission after UCBT for 5 months, she relapsed at the 6th month after UCBT. This patient achieved remission after subsequent interferon-α treatment for two weeks but eventually died of severe pneumonia. This case highlights the possibility of unusual relapse sites after chemotherapy and that regular biopsy of the mass is not sufficient to assess the scope and location of recurrence. PET/CT may be a useful tool to monitor the scope of extramedullary recurrence and follow-up remission. Further understanding of the pathology of extramedullary relapse is warranted to improve the management of such challenging presentations. This case suggests the efficacy of CAR-T cell therapy combined with UCBT in adult B-ALL patients with extramedullary relapse.